Noble Values In The Culture Of "Angngaru” Oral Traditions Of Makassar - Surjasni Surjasni; Sirajuddin Kamal (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This article explores the noble values embedded within the "Angngaru" oral tradition of the Makassar culture, which serves as an important element of the region's intangible cultural heritage. "Angngaru" is a traditional form of oral expression practiced in Makassar society, characterized by poetic recitations that convey principles of honor, bravery, loyalty, and social harmony. Through a cultural and anthropological approach, this study aims to elucidate the symbolic meanings and philosophical insights that “Angngaru” imparts, reflecting the deeply rooted values of Makassar’s collective identity. The findings demonstrate that “Angngaru” not only strengthens communal bonds but also functions as a medium for transmitting ethical teachings and local wisdom across generations. By preserving “Angngaru”, Makassar society maintains a cultural foundation that supports moral integrity and resilience amid modernity's challenges. This study contributes to a deeper understanding of how oral traditions serve as vehicles for moral and ethical teachings in Indonesian cultural landscapes, specifically within the context of Makassar.